Revisiting the dispersion safety factor (DSF) for vapor clouds of liquefied flammable gases (LNG and propane) - Agueda, Alba; Subirana, Joan; Pastor, Elsa; Miralles Schleder, Adriana [UNESP]; Planas, Eulalia (Elsevier B.V., 2020)
The concept of the Dispersion Safety Factor (DSF) was introduced by Vilchez et al. (2013, 2014) and has been revisited in this work. The DSF is defined as the ratio between the flammable region of the vapor cloud (set at a concentration equal to the low flammability level (LFL)) and the corresponding visible boundary of the cloud. We have used a computational fluid dynamics model (FLACS v.10.4) to simulate the dispersion of two liquefied flammable fuels (LNG and propane). DSF results have been analyzed using main effects and interaction plots, and a complementary metric (DSF50) has been introduced in order to establish more conservative threat areas in flammable vapor cloud scenarios. We have observed an interaction between relative humidity and wind velocity for DSF in the low-to-medium range of RH and wind velocity values. Four regression models have been proposed for the computation of DSF and DSF50 for LNG and propane dependent on ambient wind velocity and relative humidity. Contour plots have been prepared to be used as a practical tool, because through the reading of these plots the DSF (and DSF50) can be obtained immediately given wind velocity and relative humidity data.
Keywords: FLAGS; CFD simulation; Wind velocity; Relative humidity; Visible cloud